Anti-terrorism financing laws in Malaysia: current trends and developments - Abdul-Qadir Zubair, Aishat; Oseni, Umar Aimhanosi; Mohd Yasin, Norhashimah (International Islamic University Malaysia, 2015)
Malaysia has continued to proactively enhance its legal framework for combating terrorism financing as a phenomenal response to the global war against terrorism. This paper revisits the provisions relating to anti-terrorism financing in the Anti-Money Laundering and Anti-Terrorism Financing Act 2001 (AMLATFA), and the recent amendment made to the Act in 2014, as well as the Penal Code of Malaysia. While this study focuses on Anti-Terrorism Laws in Malaysia, AMLATFA forms the crux of the discussion in the light of current developments in anti-terrorism legislation in Malaysia. A brief Islamic legal perspective on anti-terrorism financing is given in the light of specific provisions of AMLATFA and the Penal Code. The paper finds that Malaysia is keeping up with the global developments in Anti-Terrorism Financing laws and this has helped it to maintain a good image in the global world as a country that is ready to combat terrorism generally and terrorism financing specifically. With the emerging threats of the self-styled Islamic State in Iraq and Levant (ISIL) in Malaysia and the world at large, there is no better time than now to come up with a more comprehensive law such as the Prevention of Terrorism Act 2015 to complement existing legislations on terrorism financing.